The combination of cantharidin and antiangiogenic therapeutics presents additive antitumor effects against pancreatic cancer. (November 2018) - Xu, Meng-Dan; Liu, Lu; Wu, Meng-Yao; Jiang, Min; Shou, Liu-Mei; Wang, Wen-Jie; Wu, Jing; Zhang, Yan; Gong, Fei-Ran; Chen, Kai; Tao, Min; Zhi, Qiaoming; et al.
Abstract Cantharidin, one of the active components of mylabris, is believed to have antitumor activity. Cantharidin selectively inhibits protein phosphatase 2A (PP2A), which can repress multiple oncogenic kinases (ERK, JNK, PKC, and NF-κB). Researches in vitro have shown that cantharidin suppresses cell viability and metastasis in pancreatic cancer cells. This study aims to investigate the effects of cantharidin on pancreatic cancer xenografts in vivo. Xenograft models were established using cells stably expressing luciferase. Xenograft growth was evaluated by living imaging. Gene expression was determined using a microarray, real-time PCR, a RayBiotech antibody array, and the Milliplex assay. Surprisingly, cantharidin significantly accelerated xenograft growth. Living imaging showed a rapid distribution of D-luciferin in cantharidin-treated xenografts, suggesting a rich blood supply. Immunohistochemistry confirmed increased angiogenesis. Microarray and antibody array identified upregulated proangiogenic and downregulated antiangiogenic factors. The Milliplex assay suggested elevated secretion of IL-6, IL-8, TNF-α, and VEGF. Inhibitors of ERK, JNK, PKC, and NF-κB pathway attenuated the cantharidin-induced changes to proangiogenic gene expression. PKC pathway-inhibiting tamoxifen or antiangiogenic therapeutics, including Ginsenoside Rg3, bevacizumab, Apatinib, and Endostar, antagonized the proangiogenic effect of cantharidin or its derivatives. These regimens presented remarkable additive antitumor effects in vivo. Although cantharidin presents antitumor effects in vitro and has been applied in clinical practice, we revealed an unfavorable proangiogenic side effect. We recommend that the clinical application of cantharidin should be performed on the premise of antivascularization therapy.